Evaluation of the Prevalence and Risk Factors of Dry Eye in Young Population - Rupal Bhatt; Vaishali Prajapati; Urvi Viramgami (Delhi Journal of Ophthalmology)
Purpose: To evaluate prevalence and causative risk factors of dry eye in pediatric population. Methods: It was a prospective observational study, conducted in 500 patients (1000 eyes), who visited at outpatient department of pediatric ophthalmology of our tertiary eye care center. All patients were screened for ocular surface disease index. Of those, having score >13 were further evaluated for the dry eye tests. The 60 eyes of 30 patients were selected and studied for the causes, types of dry eye. Results: Out of 500 out patients, 30 patients (60 eyes) have >13 score, with clinically proven bilateral dry eye. The most commonly affected age group was 7-18 years. The most common association were Vernal Kerato-Conjunctivitis (VKC), Meibomian Gland Dysfunction (MGD) & Computer Vision Syndrome (CVS)- as over use of mobile. Conclusion: The evaporative dry eye due to MGD & CVS is common in pediatric age group, while the aqueous deficiency dry eye is not so. The use of mobiles, tablets, computers leads to increase the rate of dry eye in children, which also affect the outdoor activity, study of child & child over all development.